THE INFLUENCE OF MARKETING COMMUNICATION ON SALES IMPROVEMENT OF PT. GARUDA INDONESIA AIRWAYS - Manengkey, Regina; Tielung, Maria (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
One of the faster changes that happen in Indonesia at last several years is the growth rate of airline industry. The role of Marketing Communications is important to improve and maintain the company's position in the market is reflected in the company's market share. This research aims to understand and extend the knowledge about the impact of marketing communications on sales improvement of PT. Garuda Indonesia Airways. This research uses causal type of research where the research methods associative with regression analysis. The result shows that Sales Promotion, Advertising, and Personal Selling do not have significant influence, while Direct Marketing has significant influence on sales improvement of PT. Garuda Indonesia Airways. The marketing divisions of PT. Garuda Indonesia Airways should be more focus on sales promotion, advertising and personal selling variables to get more intention of consumers. On the other hand, management of Garuda Indonesia Airways also needs to evaluate their advertising strategies so it can increase tickets purchases by consumer. Keywords: sales, promotion, advertising, personal selling, direct marketing